2013
DOI: 10.4236/ijohns.2013.22018
|View full text |Cite
|
Sign up to set email alerts
|

Steimann Pin Repair of Zygomatic Complex Fractures

Abstract: Purpose: To present the treatment of zygomaticomaxillary complex (ZMC) fractures with closed-reduction Steinmannpin fixation and to compare it to the reduction and aesthetic outcomes of open-reduction techniques (ORIF). Materials and Methods: Case series. Charts for 23 patients with ZMC fractures presenting to the Head and Neck Surgery Department at Harbor-UCLA Medical Center from 2005 to 2009 were reviewed. Pre-and post-operative computed tomography (CT) scans were analyzed. Follow up ranged from 3 to 55 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Many studies have shown that young adult males were commonly affected. [ 6 10 8 ] Two hundred and thirteen (86%) patients were male and 32 (10%) patients were female [ Table 1 ]. Ninety-eight (40%) patients had left side and 147 (60%) had right sided fractures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that young adult males were commonly affected. [ 6 10 8 ] Two hundred and thirteen (86%) patients were male and 32 (10%) patients were female [ Table 1 ]. Ninety-eight (40%) patients had left side and 147 (60%) had right sided fractures.…”
Section: Resultsmentioning
confidence: 99%
“…However, three-point wire fixation was only slightly less stable. [ 8 ] Mixing wires with miniplates reduced the stability in proportion to the number of wires used. Minimal increases in stability were added using three-point miniplate fixation when compared to two-point miniplate fixation, regardless of the application site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that it is a desirable approach for undisplaced zygomatic fractures due to its simple, effective, and cosmetically acceptable results. In 2013, Salinas et al 15 treated 23 patients with zygomaticomaxillary complex fractures using a closed reduction method with Steinmann-pin fixation. They compared their outcomes (reduction and esthetic) with those of patients who underwent open reduction and internal fixation (ORIF) techniques.…”
Section: Closed Methods Of Reduction and Fixationmentioning
confidence: 99%
“…Zhang et al (2018) reported comparable mean age of 33.6±11.4 years in Chinese such patients [14] while Ogata et al (2013) reported it to be 39.8±17.0 years in Japan [15]. Salinas et al (2013) observed it to be 40.3±7.9 years in such patients in USA [16].…”
Section: Discussionmentioning
confidence: 92%